Filter circuits mobile application - He, Linshan (Nanyang Technological University, 2022)
Digital technologies especially mobile phones have become a necessary tool for everyone, but notably for students as they seek internet resources to enhance learning outside of school environment. Thus, the main objective of this project is to build a mobile application that educates students about filter circuits and inspires them with its real-life application using React Native Expo CLI, Firebase and SQLite. The secondary objective is to serve as an advisor for circuit designers. Fundamentals, ideal filters, types of filters (passive and active), order of filters, and applications of filters are among the topics covered by the mobile application FilterEdu in this project regarding the four main filters (low-pass, high-pass, band-pass, and band-stop filters). Texts, images, and videos are used to display this content. In addition, FilterEdu educates through social and interactive features like forums, quizzes, and basic graphing of first order RC low-pass and high-pass circuits. This report details the front-end and back-end development of FilterEdu features and recommendations for future work.